Follicular dendritic cell differentiation is associated with distinct synovial pathotype signatures in rheumatoid arthritis - El Shikh, Mohey Eldin M.; El Sayed, Riham; Aly, Nesreen Amer Ramadan; Prediletto, Edoardo; Hands, Rebecca; Fossati-Jimack, Liliane; Bombardieri, Michele; Lewis, Myles J.; Pitzalis, Costantino (Frontiers in Medicine, 2022)
Follicular dendritic cells (FDCs) fundamentally contribute to the formation of synovial ectopic lymphoid-like structures in rheumatoid arthritis (RA) which is associated with poor clinical prognosis. Despite this critical role, regulation of FDC development in the RA synovium and its correlation with synovial pathotype differentiation remained largely unknown. Here, we demonstrate that CNA.42+ FDCs distinctively express the pericyte / fibroblast-associated markers PDGFR-b, NG2, and Thy-1 in the synovial perivascular space but not in established follicles. In addition, synovial RNA-Seq analysis revealed that expression of the perivascular FDC markers was strongly correlated with PDGF-BB and fibroid synovitis, whereas TNF-a/LT-b was significantly associated with lymphoid synovitis and expression of CR1, CR2, and FcgRIIB characteristic of mature FDCs in lymphoid follicles. Moreover, PDGF-BB induced CNA.42+ FDC differentiation and CXCL13 secretion from NG2+ synovial pericytes, and together with TNF-a/LT-b conversely regulated early and late FDC differentiation genes in unsorted RA synovial fibroblasts (RASF) and this was confirmed in flow sorted stromal cell subsets. Furthermore, RASF TNF-aR expression was upregulated by TNF-a/LT-b and PDGF-BB; and TNF-a/LT-b-activated RASF retained ICs and induced B cell activation in in vitro germinal centre reactions typical of FDCs. Additionally, FDCs trapped peptidyl citrulline, and strongly correlated with IL-6 expression, and plasma cell, B cell, and T cell infiltration of the RA synovium. Moreover, synovial FDCs were significantly associated with RA disease activity and radiographic features of tissue damage. To the best of our knowledge, this is the first report describing the reciprocal interaction between PDGF-BB and TNF-a/LT-b in synovial FDC development and evolution of RA histological pathotypes. Selective targeting of this interplay could inhibit FDC differentiation and potentially ameliorate RA in clinically severe and drug-resistant patients.